Intercultural Competence in Intercultural Service Encounters: Case of a Language School in France - Jerinic, Zorana (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This article aims to study the intercultural competence (IC) of service providers of an SME, as little is known about its role in the intercultural service encounters (ICSE). To be considered effective, service providers must adapt to their interlocutors by the means of communication competence, as services are intangible. Service encounters between culturally different providers and customers being more and more intense, it is necessary to consider service providers’ IC, defined as an ability to negotiate cultural meanings. The results of our case study indicate that IC in services is enhanced by their characteristics and is therefore strongly context-dependent.